1990
DOI: 10.1620/tjem.160.145
|View full text |Cite
|
Sign up to set email alerts
|

T1 and T2 relaxation times on gadolinium-diethylenetriaminepentaacetic acid enhanced magnetic resonance images of brain tumors.

Abstract: MRI of brain tumors was performed with CPMG pulse sequence, and T1 and T2 relaxation times were measured before and after the administration of 0.1 mmol/kg Gd-DTPA. T1 and T2 became significantly shorter than before with the T1 shortening being about twice the T2's. Three types of T2 shortening were classified by the difference in the intra-tumoral transport of Gd-DTPA in the time-course study after the administration. Transportal activity of Gd-DTPA seemed to be reflected by the physiologic viability of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Dynamic contrast-enhanced (DCE) MRI studies suggest increased permeability in non-enhancing WMLs and NAWM in patients with MS [7]. Alterations in T 1relaxation time, which is shortened in the presence of gadolinium [8], have also been used as a measure of BBB integrity. Multiple studies have found T 1 shortening in both enhancing and non-enhancing WMLs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast-enhanced (DCE) MRI studies suggest increased permeability in non-enhancing WMLs and NAWM in patients with MS [7]. Alterations in T 1relaxation time, which is shortened in the presence of gadolinium [8], have also been used as a measure of BBB integrity. Multiple studies have found T 1 shortening in both enhancing and non-enhancing WMLs [9].…”
Section: Introductionmentioning
confidence: 99%
“…2 for comparison to the data derived from the mixture model and from CT imaging only. Studies have shown in vivo the T1- and T2-shortening effects due to the use of GBCA in contrast enhancement studies, with a range from 30 to 68% shortening of T1 post administration of 0.1 mmol/kg body weight [13]. The effect of GBCA on clinically derived MR attenuation maps has recently been demonstrated [14], showing an overestimation of image-based activity concentration due to an assignment of part of the lung tissue to the soft tissue by the MRAC due to the presence of GBCA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that measurement of the change in T 2 provides important information about the mobility and chemical environment of the tissues of interest [4], [9] - [11]. Previous studies examining the utility of T 2 mapping in the context of neurologic and psychiatric disease demonstrated variations in T 2 values, sometimes very subtle, in specific brain regions within conditions of autism [12], schizophrenia [13], [14], epilepsy [15], Parkinson's [16], multiple sclerosis [17], [18], Alzheimer disease [9], tumors [19], [20], [21] and a host of other disorders [6], [14], [16], [22], [23]. Nevertheless, mapping the T 2 parameter is rarely used in clinical diagnostics, the most common reported reasons being higher scanning times [4], [6], [10], [11] or its lack of specificity, in contrast to its high sensitivity [5], [6], [17], [24].…”
Section: Introduction N Recent Years Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%